Perbaikan Kontrol Generasi Otomatis (AGC) dengan 2DOF-PID-PIID pada Dua Area Turbin Non Reheat dalam Sistem Tenaga yang Saling Terhubung - Rio Irawan; Ermanu Azizul Hakim; Haneef Nouval Alannibras Humaidi (Jurnal Penelitian Pendidikan IPA, 2025)
An efficient and reliable electric power system must be able to maintain operational stability, especially in maintaining frequency stability to remain at its nominal value, both in constant conditions and when disturbances occur. For this reason, optimal frequency control is needed through Automatic Generation Control (AGC). In AGC, a controller is needed to accelerate the frequency response so that it is quickly stabilized. This study proposes the development of a 2DOF-PID controller into a 2DOF-PID-PIID optimized using the Dandelion Optimizer (DO) to improve AGC performance in the context of Load Frequency Control (LFC). The test results show that the DO algorithm gives better results compared to the Sine Cosine Algorithm (SCA), Pelican Optimization Algorithm (POA), and Archimedes Optimization Algorithm (AOA). Therefore, DO is chosen to optimize 2DOF-PID-PIID. The 2DOF-PID-PIID controller optimized with DO produces an ITAE (Integral Time Absolute Error) value of 0.001276, which is superior compared to the 2DOF-PID (0.00158), 2DOF-PID-PID (0.00158), PID (0.001833), and PIDD (0.002022) controllers, indicating its effectiveness in accelerating the response and maintaining frequency stability in the electric power system.